Greening the workplace through supervisory behaviors: assessing what really matters to employees. Issue 9 (11th April 2022) - Paillé, Pascal; Mejía-Morelos, Jorge Humberto; Amara, Nabil; Norrin, Halilem
Abstract: Research in environmental sustainability shows consistently that supervisory support plays a critical role in shaping the work context to create conditions that favor employee eco-friendly behaviors. We investigate the combined effect of supervisory support, trust in supervisor and commitment to the supervisor for predicting employees' environmental behavior using data from a sample of 142 full-time employees in a fuzzy sets qualitative comparative analysis (fsQCA). Our findings show first, that employee environmental behaviors are motivated by supervisory support, regardless of trust in supervisor or commitment to the supervisor. Our results also show that in the absence of supervisory support, employees' environment behavior is fostered by trust in supervisor and commitment to the supervisor. This research contributes to the literature by clarifying how supervisors can encourage subordinates to behave in an eco-friendly way.